Senam Otak Mempengaruhi Fungsi Kognitif Lansia dengan Demensia - Faleri, Nafila Ayu; Hidayat, Syaifurrahman; Oktavianisya, Nelyta (STIKES Karya Husada Kediri, 2024)
Individuals when they enter the age of 60 years and over are categorized as elderly, one of the many problems in the elderly that often arise is dementia / memory loss which will then have a bad influence on cognitive function. The design of this research is quantitative with a pre-experimental approach, one group pre-posttest design. Respondents in the study were elderly with dementia. The sampling technique used purposive sampling as many as 35 elderly residents. Data collected through the SPMSQ questionnaire. Data analysis used Wilcoxon test with sig < 0.05. posttest results of giving brain exercise to the elderly. The results of the pretest giving brain exercise to the elderly. From the results of the pretest, it was found that the elderly with mild intellectual function damage were 25.7%, moderate intellectual function damage was 65.7% and severe intellectual function damage was 8.58%. From the posttest results, it was found that the elderly who had intact intellectual function were 22.86%. Mild intellectual function damage was 62.86%, moderate intellectual function damage was 11.7% and the elderly who experienced severe intellectual function damage were 2.85%. Data analysis shows the value of Asymp. Sig. worth 0.000. Because the value of 0.000 is smaller than 0.05, it can be concluded that there is an effect of giving brain exercise therapy to the elderly. Regular giving of brain exercise to the elderly can have a good impact on improving the cognitive function of the elderly. Therefore, elderly exercise is recommended to be a therapy that is also given to the elderly because it does not have side effects.